COD and ammonia removal from landfill leachate using mixed granular adsorbent media - Daud, Zawawi; Abubakar, Mahmoud Hijab; Abdul Latiff, Ab Aziz; Awang, Halizah; Ahmad, Zulkifli; Ridzuan, Mohd Baharudin (UTM Press., 2018)
Landfills generate leachate that contains elevated concentration of contaminants and is hazardous to human health and the ecosystem. In this study, the mixture of granular feldspar and cockle shells was investigated for remediation of COD and ammonia from landfill leachate. All adsorbent media were sieved to a particle size between 2.00 and 3.35 mm. The results revealed that the optimum mixing ratio of feldspar and cockle shells was 20:20, shaking speed was 150 rpm, pH level was 6, shaking time was 120 min, and dosage was 30 g. The adsorption isotherm analysis reveals that the Langmuir isotherm yielded the best fit to experimental data as compared to the Freundlich isotherm. The media produce encouraging results and can potentially be used as a good and sustainable adsorbent.